Allergen immunotherapy for house dust mite: clinical efficacy and immunological mechanisms in allergic rhinitis and asthma. (November 2013) - Eifan, Aarif O; Calderon, Moises A; Durham, Stephen R
<x xml:space="preserve">Abstract</x> Introduction: There is an increasing prevalence of atopic diseases such as allergic rhinitis and asthma with house dust mite (HDM) being the common allergen that is highly associated with allergic rhinitis and asthma. Allergen avoidance and pharmacotherapy are part of treatment but it has proved difficult to change the course of HDM-related allergic diseases. Allergen immunotherapy (AIT) has been in use for the past century and has been shown to be effective in the treatment of allergic respiratory disease. Areas covered: This review exclusively focuses on HDM-AIT and discusses the differences in clinical efficacy and safety, long-term effect after discontinuation and immunological changes observed in both HDM-subcutaneous immunotherapy (SCIT) and HDM-sublingual immunotherapy (SLIT) in the treatment of allergic rhinitis and asthma in both pediatric and adult populations. Expert opinion: The majority of studies involved small numbers of patients, variable doses of major allergens and are of variable quality. There is good evidence for HDM-SCIT efficacy and its long-term effect in adults and children, whereas at the present time, evidence for HDM-SLIT is unconvincing, particularly in children. In carefully selected patients, HDM-SCIT is effective and safe. More definitive trials are needed before HDM-SLIT can be recommended in routine practice for rhinitis and/or asthma.